2015
DOI: 10.1158/0008-5472.can-14-1726
|View full text |Cite
|
Sign up to set email alerts
|

Usp28 Counteracts Fbw7 in Intestinal Homeostasis and Cancer

Abstract: The stability of several oncoproteins, including c-Myc, is regulated by ubiquitin-dependent degradation mediated by the SCF (Fbw7) ubiquitin ligase. This activity is antagonized by the deubiquitinase Usp28, which is highly expressed in murine and human intestinal cancers. Usp28 was previously shown to interact with its substrates via a "piggyback" interaction with Fbw7, which suggested that Fbw7 is required for Usp28 activity. Unexpectedly, we found that genetic deletion of Usp28 rescued the lethality of Fbw7-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
66
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 20 publications
(36 reference statements)
2
66
0
Order By: Relevance
“…Using peptide binding assays, it was shown that USP28 binds to the same Myc phosphodegron recognized by Fbw7 in MBI; yet USP28 binds to the non-phosphorylated form whereas Fbw7 binds to the phosphorylated form of this Myc degron. 58 These studies demonstrate a complex regulation of Myc by the USP28-Fbw7 interplay, suggesting an important role in the dynamic and finely tuned regulation of Myc activity necessary for normal cellular function.…”
Section: Deubiquitination Of Myc: When and Where?mentioning
confidence: 80%
See 2 more Smart Citations
“…Using peptide binding assays, it was shown that USP28 binds to the same Myc phosphodegron recognized by Fbw7 in MBI; yet USP28 binds to the non-phosphorylated form whereas Fbw7 binds to the phosphorylated form of this Myc degron. 58 These studies demonstrate a complex regulation of Myc by the USP28-Fbw7 interplay, suggesting an important role in the dynamic and finely tuned regulation of Myc activity necessary for normal cellular function.…”
Section: Deubiquitination Of Myc: When and Where?mentioning
confidence: 80%
“…57 Further complexity was revealed in an intestine study, where it was shown that deletion of USP28 rescued the cytotoxic effects of Fbw7-deficiency in primary fibroblasts and meliorated the hyperproliferation and the impaired goblet and Paneth cell differentiation in mice with intestine-specific deletion of Fbw7 (Fbw7 DIEC ). 58 This correlates with correcting the aberrant accumulation of Fbw7 substrates such as Myc, c-Jun and NICD1. These results suggest that USP28 can function independent of a direct interaction with Fbw7.…”
Section: Deubiquitination Of Myc: When and Where?mentioning
confidence: 96%
See 1 more Smart Citation
“…Pulldown experiments using c-Myc peptides showed that USP28 and Fbw7 bind to the phosphorylated CPD motif; however, USP28 only bound to non-phosphorylated peptide in the absence of Fbw7 [91]. This suggests that the phosphorylated CPD motif is specifically recognised by Fbw7, which can then recruit USP28, but in the absence of Fbw7, USP28 interacts with the unmodified substrate.…”
Section: Counteracting Fbw7 Activity: Dubsmentioning
confidence: 98%
“…Moreover, inactivation of USP28 in established APC min/+ tumours reduced c-Myc protein levels, decreased tumour cell proliferation, and increased tumour cell differentiation and death, resulting in increased life expectancy. A follow up study investigated the potential benefit of inactivating USP28 in Fbw7-deleted colorectal cancers [91], as this situation is commonly found in patients. Protein levels of the Fbw7 substrates c-Myc, c-Jun, NICD1 and cyclin E1, which were all elevated in Fbw7-deleted mice, were downregulated in double knock out animals.…”
Section: Counteracting Fbw7 Activity: Dubsmentioning
confidence: 99%